2016
DOI: 10.1163/15685381-00003073
|View full text |Cite
|
Sign up to set email alerts
|

Body size and age structure of the endangered Clark’s lizard (Darevskia clarkorum) populations from two different altitudes in Turkey

Abstract: We investigated age structure, body size and longevity in two breeding populations of Darevskia clarkorum inhabiting altitudes ranging from 450 m a.s.l. (Kamilet) to 2250 m a.s.l. (Başyayla) in Turkey by skeletochronology performed on the phalanges. The mean age was found to be 6 years in the Kamilet population and 7 years in the Başyayla population. The maximum life span was 10 years in the lowland population while it was 12 years in the highland population. Age at sexual maturity of both males and females wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 24 publications
2
7
0
2
Order By: Relevance
“…However, according to some other authors (Fitch, 1981;Best & Gennaro, 1984) the main reason for sexual dimorphism may be related to natural selection via competition for food among individuals (Fairbairn, 1997). Consistent with this trend, in this study and other studies conducted in the same region (Bülbül et al, 2016a(Bülbül et al, , 2016b, a low level of male-biased sexual size dimorphism was observed for the relevant lizards. Contrary to these results, Gül et al (2014) reported strong female-biased SSD in the highland population of D. rudis, whereas SSD appeared male-biased, although not statistically significant, in the lowland populations.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, according to some other authors (Fitch, 1981;Best & Gennaro, 1984) the main reason for sexual dimorphism may be related to natural selection via competition for food among individuals (Fairbairn, 1997). Consistent with this trend, in this study and other studies conducted in the same region (Bülbül et al, 2016a(Bülbül et al, , 2016b, a low level of male-biased sexual size dimorphism was observed for the relevant lizards. Contrary to these results, Gül et al (2014) reported strong female-biased SSD in the highland population of D. rudis, whereas SSD appeared male-biased, although not statistically significant, in the lowland populations.…”
Section: Discussionsupporting
confidence: 91%
“…The lifespan of some species of the genus Darevskia whose demographic characteristics have been studied varies between 6 and 12 years. Among them, the species D. rostombekowi, D. dahli (Arakelyan & Danielyan, 2000), D. sapphrina (Arakelyan et al, 2013), D. uzzeli (Arakelyan et al, 2013) and D. bithynica (Gül et al, 2015) live for six years, D. armeniaca (Arakelyan et al, 2013), D. unisexualis (Arakelyan et al, 2013), D. rudis (Gül et al, 2014) and D. parvula (Bülbül et al, 2016b) live up to eight years and D. clarkorum (Bülbül et al, 2016a) lives up to 12 years. We found that the oldest individuals in the studied Hopa population are nine years old.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The relationship between age and body size is an important life-history parameter that is frequently used in demographic surveys (Kurnaz et al 2018). Our findings show that the age of specimens was positively correlated with their body size (SVL) as in many rock lizards (D. clarkorum, Bülbül et al 2016b;D. valentini, Kurnaz et al 2017;D.…”
Section: Discussionsupporting
confidence: 64%
“…The known localities of the species were very scarce in this distribution area. After the description of the species, a few studies including taxonomy, morphology, distribution and ecology were performed about it (Franzen, 1990(Franzen, , 1991Darevsky & Tuniyev, 1997;Sindaco et al, 2000;Schmidtler et al, 2002;Ilgaz, 2007;Bülbül et al, 2016). The present study aims to add a new province and new locality to the distribution area of the species.…”
mentioning
confidence: 99%